Installment purchase and its social dimensions Afield study in Mosul city - Assist .prof .Dr . Ameerah Waheed Katab (Journal of College of Education, 2024)
Installment research summary Purchasing through installments is a type transaction that the citizen needs as a solution to meet the family’s needs due to the weak purchasing power of the citizen and the lack of cash flow. At the same time, merchants seek to dispose of their goods in a new method in our society in the city of Mosul. The importance of research lies knowing the effects of this installment payment on the family positively and negatively. As for the research objectives, identifying the social and economic reasons that make people turn towards installments, an intentional random sample of (100) families was chosen that practiced purchasing through installments, and the social survey approach was followed. As for research tools, they were the questionnaire form, the interview, and observation. The results of the research resulted in the following: • One of the positives of buying in installments is that it is easy to provide many household needs that the family cannot buy in one payment. • The abundance of imported and modern goods in the markets prompts the citizen to desire to acquire and purchase these goods, which prompts him to use the installment system. • The rise in commodity prices leads to the use of the installment system. • The large number of installment leads to a deficit in the family budget. Key words: The purchase, Installment system, social dimensions , positive effects , Negative effects , In cash